PEMANFAATAN MEDIA GAMIFIKASI DIGITAL UNTUK MENINGKATKAN JOYFUL LEARNING DALAM PEMBELAJARAN IPS DI SMP NEGERI 3 TAROGONG KIDUL - Rahman, Firman; Tetep (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of digital gamification media in improving joyful learning in social studies learning at SMP Negeri 3 Tarogong Kidul. The background of this research is the low level of student engagement and learning motivation in social studies classes. This research used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The sample consisted of two classes, namely the experimental class and the control class. Data were collected through questionnaires, observations, and learning outcome tests. The results showed that the use of digital gamification media significantly improved students’ joyful learning and learning outcomes compared to conventional learning. Therefore, digital gamification media can be used as an alternative learning strategy to create a fun and meaningful learning environment. Keywords: digital gamification, joyful learning, social studies learning